The association between Emotional Regulation and Internet Gaming Disorder. (July 2020) - Lin, Pei-Yun; Lin, Hung-Chi; Lin, Pai-Cheng; Yen, Ju-Yu; Ko, Chih-Hung
Highlights: Emotion adjustment is significantly negatively associated with Internet Gaming Disorder. Emotion adjustment moderates the association between emotion concealment and Internet Gaming Disorder. We believe the numerous problems arising from Internet Gaming Disorder could be partially resolved by employing emotion-focused therapy to intervene in the emotion-regulation deficit. Abstract: Purpose: Lack of control over Internet gaming habits may result in negative consequences. This study aimed to evaluate the emotional regulation of adults with Internet gaming disorder (IGD) and the association of emotion regulation, depression, and hostility. Methods: Advertisements were used to recruit 69 young adults with IGD, 69 sex- and age-matched controls, and 69 sex- and age-matched regular gamers. The diagnosis of IGD was according to diagnostic interviews based on DSM-5 IGD research criteria. Participants completed the Affective Style Questionnaire, the center of epidemiological studies depression scale and the short-form Chinese version of Buss-Durkee Hostility Inventory. Results: In the IGD group, the emotion adjustment score was significantly lower, whereas the scores for depression, and hostility were significantly higher than in the other two groups. In addition, emotion adjustment is the most associated emotion regulation behavior of IGD, followed by emotion concealment. In IGD group, emotion adjustment had a negative correlation with depression and hostility. Conclusions: Our study demonstrate that emotion adjustment is significantly associated with IGD. The depression and hostility mediated the association. Knowing that emotion adjustment plays a critical role in IGD, future interventions should focus on this subscale of emotion regulation.